PRIORITY DIRECTIONS OF FAMILY POLICY IN THE REPUBLIC OF UZBEKISTAN - Ibragimova Zulfiya (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
the article considers the main priority directions of family policy in the Republic of Uzbekistan, the role of the family in society, as well as legislatively fixed consistent measures to protect the family, motherhood and childhood.